Islamic ethical principles to protect environment affected by modern biotechnology - Nur Asmadayana Hasim,; Latifah Amin,; Zurina Mahadi,; Nor Ashikin Mohamed Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Malaysian government strongly promotes research and development in modern biotechnology since it has the potential to bring economic benefits to the nation. Modern biotechnology has been associated with several ethical issues related to the environment. This leads to the need for having appropriate laws and guidelines for governance purposes. There is a legal vacuum in the existing Biosafety Act 2007. This Act focuses on scientific risk assessment concerning modern biotechnology and does not contain any provision in terms of the social and ethical aspects of modern biotechnology. The objective of this article is to identify and select the core ethical principles that are both acceptable, and capable of protecting the environment. By using a qualitative approach, a series of focus group discussions (FGD) were conducted consisting of four groups of stakeholders in biotechnology. The discussions were recorded, transcribed and analyzed thematically. The research findings show that the stakeholders strongly agree on the importance of three ethical principles for protecting the environment. They fully support the adoption of these ethical principles as the guiding principles for developing Malaysian Ethical Guidelines for Modern Biotechnology in the future. This research links Islamic and Western-based ethical principles in relation to the environment and its protection.